The Effect of Kangaroo Care on Body Temperature Stability of Low Body Weight : Literature Review - Ruminem, Ruminem; Adawiyah, Jamiatul; Widiastuti, Ida Ayu Kade Sri; Sari, Rita Puspa; Ramadhani, Siti (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Background : Low Birth Weight Babies (LBW) are babies born with birth weight <2500  grams  regardless  of gestational age. One  of the complications of LBW is the  instability  of  body  temperature,   so   to   maintain  its  stability  the  kangaroo method  of  care  is  used. The  purpose of this  study is u ntuk  identify  and  analyze articles related  to  the kangaroo  method  of treatment influences the stability of the baby's body temperature  LBW. Methods   of study : This   study   is   a   literature review   premises  using   the   3 articles that are tailored  to the inclusion  criteria  and were analyzed  methods critical appraisal . Research Results : Based  on the results of the research, the three articles showed that the characteristics of the majority of respondents were female, aged 3-28 days and   the   majority   weighed   1500-2000   grams. There  is  a  difference  in  body temperature  of  LBW  babies  before  and  after  Kangaroo  Method  Treatment  and there  is  an  effect  of  Kangaroo   Method   Care  on  the  stability  of  the  body temperature of LBW babies. Conclusion :   There is differences  in  body  temperature  of  LBW  before  and  after  being given kangaroo   method   treatment  and  there  is  an  effect  of  kangaroo  method  care on body temperature of LBW babies..